Soil organic carbon stocks in the forests of different continents - Gachhadar, Pramila; Baniya, Chitra Bahadur; Mandal, Tejnarayan (Our Nature, 2022)
Carbon stocks in soil vary substantially across the globe depending on the type of forests, their locations, and soil depths. We applied meta-analysis to 64 relevant published data with no restriction of published date, country, and journals. However, it was always kept in mind to include high impacted journals. The aim of this review was to evaluate whether soil organic carbon (SOC) varies with forest types, soil depths, and altitudes. Globally, the SOC stocks in the forests were found in the order of Boreal forest (BF) > Subalpine forest (SAF) > Temperate forest (TeF) > Afromontane forest (AfMF) > Montane forest (MF)> Subtropical forest (SF) > Alpine forest (AF) > Tropical forest (TF) ranging from 64.3 t/ha to 206.6 t/ha, the minimum is in tropical forest and maximum in the boreal forest. The SOC stocks were also found varied with soil depths and forests of different continents too. The maximum value of SOC stocks was 366.94 t/ha in 0-40 cm soil depth and the minimum value was 20.16 t/ha in the 80-100 cm soil depth. Linear relationship of SOC stocks was obtained with altitudes, the value increases along the increasing elevations. In conclusion, SOC stocks varied as forests, soil depths, and elevations as well.